A case study on change dimensions, factors and models in a private services sector, India - Sanjeevkumar, Virmala (Social Science Research Network (SSRN), 2011)
Change management has received considerable attention in human resource management. A strong and effective organization must be able to both pro act and react with flexibility to changing environmental demands.Change management can be viewed from two perspectives - from those implementing the change and from the recipients of change. GKNM Hospital wants to explore the models of Change management and assist the process of Change management and it wanted to improve its Business and Service performance. The three dimensions which were considered for the research are structure, technology and people.GKNM Hospitals made a conscious effort to identify the priority area of Change Management practices.The researcher used dependent and independent variable and various statistical tools and applied change models based on the inferences.Change management in GKNM involves formulation of Change models, Key performance areas and strategies to ensure that it is an integral part of HR strategy.